DESIGNING COMPUTER-BASED SUMMATIVE TEST FOR THE ELEVENTH GRADE STUDENTS - Johan, Joni; ., Ikhsanudin; Supardi, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This study aimed at designing Computer-Based Summative Test software as a tool to support English Test. To make sure that the learning objectives are fulfilled, the testing materials should be in line with the curriculum and learners’ needs. This study was attempted to design reading testing software based on teachers’ and students’ needs. The software was designed because it can solve the testing problems.  In this research, the researcher uses ADDIE approach where the participants are the teachers and the eleventh grade students of SMA Sentosa Pemangkat. This study found that students’ summative tests need a new testing system which can randomize test items and fasten test result publishing. The result showed that the software can be used by the teacher and students as a software to test students’ reading achievement in summative test. The researcher suggests that the teachers use this software to help them in testing. Keywords: Computer-Based Summative Test, ADDIE Approach   Abstrak: Penelitian ini bertujuan untuk mendesain program Ujian Sumatif berbasis komputer sebagai sebuah perangkat untuk mendukung Ujian Bahasa Inggris. Untuk memastikan bahwa tujuan pembelajaran dapat tercapai, maka bahan ujian harus sesuai dengan kurikulum dan kebutuhan siswa. Penelitian ini bertujuan untuk merancang program ujian membaca berdasarkan kebutuhan guru dan kebutuhan siswa. Program ini dirancang karena ia bisa menyelesaiakn masalah dalam ujian. Penelitian ini menggunakan pendekatan ADDIE dimana pesertanya adalah guru dan siswa kelas XI di SMA Sentosa Pemangkat. Penelitian ini menemukan bahwa ujian sumatif memerlukan sebuah sistem yang dapat mengacak butir soal dan mempercepat pengumuman hasil ujian. Hasil penelitian ini menunjukkan bahwa program tersebut dapat digunakan oleh guru dan siswa sebagai sebuah program untuk menguji pencapaian kemampuan membaca siswa di ujian sumatif. Peneliti menyarankan agar guru menggunakan program ini untuk membantu mereka dalam ujian. Kata kunci: Ujian Sumatif Berbasis Computer, Pendekatan ADDIE